2020
DOI: 10.1093/milmed/usz476
|View full text |Cite
|
Sign up to set email alerts
|

An Attempt to Utilize the Body Composition Analyzer and the Functional Movement Screen (FMS) Test to Determine Injury Risk in Soldiers

Abstract: Introduction Injuries are the most significant health problem of military services. Military medical surveillance data are useful for determining the magnitude and causes of the injury problem, identifying possible prevention targets and monitoring trends among military personnel. Soldiers serving in the Polish Armed Forces took part in the research. The aim of the study was to identify the most common injuries of the musculoskeletal system and to analyze causes of injuries. An additional goa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Body composition analyzers are instruments used to assess the body composition index through directly measuring or using statistical methods. They can measure various health indices of patients, such as weight, basal metabolic rate, bone mass, muscle mass, visceral fat level, etc., and infer the patient’s body age, body fat percentage, and degree of obesity ( 25 - 27 ). Additionally, body composition analyzers can provide precise health indices for the upper, lower, left, and right limbs of patients, effectively indicating various health indicators.…”
Section: Discussionmentioning
confidence: 99%
“…Body composition analyzers are instruments used to assess the body composition index through directly measuring or using statistical methods. They can measure various health indices of patients, such as weight, basal metabolic rate, bone mass, muscle mass, visceral fat level, etc., and infer the patient’s body age, body fat percentage, and degree of obesity ( 25 - 27 ). Additionally, body composition analyzers can provide precise health indices for the upper, lower, left, and right limbs of patients, effectively indicating various health indicators.…”
Section: Discussionmentioning
confidence: 99%
“…Further, only two of the 14 studies assessed associations in personnel beyond the recruitment period (i.e., ≥ 90 days post accession) ( 35 , 36 ). Bertrandt et al (2020) examined lower body muscle symmetry in relation to MSKI in Polish Armed Forces soldiers ( n = 504) and found those with asymmetrical distribution of lower body lean mass were at greater MSKI risk, as assessed by self report injuries and functional movement screen (FMS) ( 28 ). In a group of Explosive Ordnance Disposal (EOD) Technicians ( n = 64), Hernandez and colleagues (2020) found that those with higher %BF, as assessed via DXA, and lower cardiorespiratory fitness (VO 2 max) had lower FMS and Y-Balance Test scores and thus greater injury risk ( 29 ).…”
Section: Body Composition Health and Weight Cycling In Military Perso...mentioning
confidence: 99%
“…The relationship between body composition, weight cycling, and health is a complex topic as health is often defined using a range of variables. In military personnel, body composition and health has only been examined in six studies (26)(27)(28)(29)(30)(31) whereas weight cycling has only been examined in the context of disordered eating (32, 33). Thus, evidence in the military population is limited.…”
Section: Body Composition Health and Weight Cycling In Military Perso...mentioning
confidence: 99%